2020
DOI: 10.11604/pamj.2020.37.9.22211
|View full text |Cite
|
Sign up to set email alerts
|

A perception survey on the roles of nurses during triage in a selected public hospital in Kwazulu-Natal Province, South Africa

Abstract: Introduction triage is gradually becoming an autonomous nursing role essential to patients' safety and the efficient delivery of emergency care. The increased need for more holistic and advanced care during triage makes the role of nurses during triage highly indispensable. However, several studies have shown that nurse-led triage has been so successful over the years in most African countries and in other developing countries. South African Triage Scale (SATS) is an example of triage tool that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…Simultaneously, they have to judge and consider available resources to optimize the provision of safe and quality patient care in the emergency department. Similarly, other researchers pointed out that the TN is expected to prioritize patients appropriately, in a suitable timeline, to provide health care education when needed and to ensure a safe environment for the patients and employees in the waiting room and throughout the emergency department (Aloyce et al, 2014 ; Bijani et al, 2020 ; Cotič Anderle & Bračko, 2019 ; Ebrahimi et al, 2016 ; Olofinbiyi et al, 2020 ). A survey conducted in Slovenia showed that nurses believe that at least 2–10 years of work experience is needed to perform triage activities effectively (Cotič‐Anderle, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, they have to judge and consider available resources to optimize the provision of safe and quality patient care in the emergency department. Similarly, other researchers pointed out that the TN is expected to prioritize patients appropriately, in a suitable timeline, to provide health care education when needed and to ensure a safe environment for the patients and employees in the waiting room and throughout the emergency department (Aloyce et al, 2014 ; Bijani et al, 2020 ; Cotič Anderle & Bračko, 2019 ; Ebrahimi et al, 2016 ; Olofinbiyi et al, 2020 ). A survey conducted in Slovenia showed that nurses believe that at least 2–10 years of work experience is needed to perform triage activities effectively (Cotič‐Anderle, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This generally aligned with the findings in previous studies. 19,27,28 However, only about 42% of participants believed that the SATS was consistent and not user dependent. This unfavourable sentiment was also highlighted in a Ugandan study among both doctors and nurses 28 , and could be possibly due to poor training on the SATS, causing incorrect triaging which subsequently may lead to delayed care and poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Mengingat banyaknya pasien yang mengunjungi UGD, yang dapat mengakibatkan masa tunggu pasien dan keterlambatan dalam menyelesaikan situasi darurat, perawat yang bertugas di UGD harus bertanggung jawab atas penyortiran pasien (Olofinbiyi et al, 2020). Praktik mengklasifikasikan pasien menurut jenis dan tingkat keparahan kondisinya dengan mempertimbangkan ketersediaan fasilitas, staf, dan pasien potensial dikenal sebagai triase (Bazyar et al, 2019).…”
Section: Pendahuluanunclassified